PENDIDIKAN KARAKTER MELALUI TRILOGI DAN PANCA KESADARAN SANTRI PERSPEKTIF IMAM GHAZALI DALAM KEGIATAN KEPESANTRENAN - Fathor Rozi; Abdullah Abdullah; Khalifatunnisa Khalifatunnisa (Muróbbî: Jurnal Ilmu Pendidikan, 2022)
This study aims to analyze and examine the Implementation of Character Education through Trilogy and Panca Awareness of Santri in Islamic boarding school activities. This study uses a descriptive qualitative approach with the type of case study research at the Nurul Jadid Paiton Islamic Boarding School, Probolinggo. The data collection instrument in this study used observation and in-depth interviews to support the completeness of the data. The data analysis technique in this study was carried out with the stages of data collection, data reduction, data presentation, and conclusion of research results. From this study, it was found that the cultivation and application of character education was very effective in the scope of the pesantren, this was reflected in the application of the principles of the pesantren, namely the Trilogy and Panca Awareness of the Santri which were recorded through Islamic boarding school activities and in line with the concept of Imam Ghazali's spiritual values ??with several methods, namely the method of exemplary, habituation, advice, and stories or stories. This research shows that the values ??of Islamic boarding schools are a full supporter in the successful implementation of character education with a complete pesantren component, of course with consistent effort and full discipline.